English language teaching to young learners in the socially distanced classroom: A critical review - Banu, Syeda Noorie; Palukuri, Vijayababu; Mutyala, Suresh; Kumar, K. Vinay (Linguistics and Culture Review, 2021)
It is understood by the academic communities that they take responsibility for their online learning with the help of the necessary technical equipment during the lockdown times, and manage their schedules. They have no choice but to find a solution to their problems on their own when their classmates and their language teachers are around. As the detention is partially lifted in some places, young students are starting to attend their language classes. In a way, they are released from the sense of isolation they felt at home during this time of Lockdown that was coming to an end. But things have changed. Now they find the common space of the classroom again, but in the socially distant classroom and also referred by some as a virtual classroom. This is a challenging time for an English teacher too. The communicative classroom has changed. How it would be possible to regain the enthusiasm of students who work together and share broad and meaningful interaction? Group discussions and pairwork can be very difficult, and young students may need to find new ways to combine these activities.